Determinants of the internationalization of multinational firms in emerging countries : a comparison of Indian and Chinese FDI in Central Africa - (:unkn) unknown (My University, 2022)
During the first two decades of the 21st century, African countries, in general, and those of Central Africa, in particular, have recorded significant economic flows from China and India. By focusing specifically on Chinese and Indian FDI flows in Central Africa between 2000 and 2019 and taking into account the heterogeneity of the behaviors of the actors involved in these relations, this thesis addresses the question of the internationalization of firms in a comparative approach in order to analyze the complexity of the phenomenon based on the interrelationships and differences that could exist between the different actors at the heart of the phenomenon studied. To this end, the first comparative study presented in this thesis describes the trends of Indian and Chinese FDI flows and stocks in Central Africa. The second study, essentially econometric, assesses the macroeconomic level, the degree of attractiveness of Indian and Chinese FDI, taking into account the socioeconomic, political, institutional and industrial specificities of Central African countries. The third, also econometric, compares the dynamism of the actors in the process of integration of African markets and essentially highlights the points of convergence and divergence in the mechanisms of internationalization of Indian and Chinese firms towards Central Africa as well as the role and international experience of leaders and partners in the perception and facilitation of the exploitation of business opportunities offered by Central African countries. At the end of these three studies, the thesis confirms the hypothesis of a rapprochement of firms to their input market (mines, oil, agroforestry), and also that of the presence of other factors (bilateral trade relations, quality institutions, political risks, economic risks, networks of firms, acquired international experience) li
Keywords: African Research